Empowerment and Livestock Farming: A Holistic Approach to Local Communities - Ramdani, Idan (UIN Sunan Kalijaga Yogyakarta, 2023)
The study aims to investigate the impact of livestock farming on community empowerment, focusing on the integration of economic, social, and environmental dimensions. The research encompasses a case study of a sheep farming empowerment program in Karanglayung, Indramayu, West Java, which serves as a model for similar initiatives in rural areas. The methodology includes a mixed-methods approach, combining quantitative surveys and qualitative interviews with local farmers, community leaders, and stakeholders involved in the program. Data collection involved assessing income levels, food security, animal health, and social cohesion within the community. The findings reveal that the program has significantly increased farmers' income by an average of 30%, improved access to nutritious food, and enhanced animal health through targeted education and training. Additionally, the program has fostered social cohesion, with participants reporting stronger community ties and collaboration. The main conclusion drawn from the study is that a holistic approach to livestock farming can effectively empower local communities, providing economic benefits while promoting sustainable practices and social unity. This model demonstrates the potential for replication in other regions facing similar challenges. Keywords: Community Empowerment, Livestock Farming, Holistic Approach, Economic Development, Social Cohesion, Environmental SustainabilitPenelitian ini bertujuan untuk menyelidiki dampak peternakan terhadap pemberdayaan komunitas, dengan fokus pada integrasi dimensi ekonomi, sosial, dan lingkungan. Penelitian ini mencakup studi kasus program pemberdayaan peternakan domba di Karanglayung, Indramayu, Jawa Barat, yang berfungsi sebagai model untuk inisiatif serupa di daerah pedesaan. Metode yang digunakan mencakup pendekatan campuran, menggabungkan survei kuantitatif dan wawancara kualitatif dengan petani lokal, pemimpin komunitas, dan pemangku kepentingan yang terlibat dalam program tersebut. Pengumpulan data melibatkan penilaian tingkat pendapatan, ketahanan pangan, kesehatan hewan, dan kohesi sosial di dalam komunitas. Hasil penelitian menunjukkan bahwa program ini telah secara signifikan meningkatkan pendapatan petani rata-rata sebesar 30%, memperbaiki akses terhadap pangan bergizi, dan meningkatkan kesehatan hewan melalui pendidikan dan pelatihan yang terarah. Selain itu, program ini telah memperkuat kohesi sosial, dengan peserta melaporkan ikatan komunitas dan kolaborasi yang lebih kuat. Kesimpulan utama yang diambil dari studi ini adalah bahwa pendekatan holistik terhadap peternakan dapat secara efektif memberdayakan komunitas lokal, memberikan manfaat ekonomi sambil mempromosikan praktik berkelanjutan dan persatuan sosial. Model ini menunjukkan potensi untuk direplikasi di daerah lain yang menghadapi tantangan serupa. Kata Kunci: Pemberdayaan Masyarakat, Peternakan, Pendekatan Holistik, Pembangunan Ekonomi, Kohesi Sosial, Kelestarian Lingkungan